Endolithic Fungal Species Markers for Harshest Conditions in the McMurdo Dry Valleys, Antarctica - Claudia Coleine; Nuttapon Pombubpa; Laura Zucconi; Silvano Onofri; Jason E. Stajich; Laura Selbmann (Life, 2020)
The microbial communities that inhabit lithic niches inside sandstone in the Antarctic McMurdo Dry Valleys of life’s limits on Earth. The cryptoendolithic communities survive in these ice-free areas that have the lowest temperatures on Earth coupled with strong thermal fluctuations, extreme aridity, oligotrophy and high levels of solar and UV radiation. In this study, based on DNA metabarcoding, targeting the fungal Internal Transcribed Spacer region 1 (ITS1) and multivariate statistical analyses, we supply the first comprehensive overview onto the fungal diversity and composition of these communities sampled over a broad geographic area of the Antarctic hyper-arid cold desert. Six locations with surfaces that experience variable sun exposure were sampled to compare communities from a common area across a gradient of environmental pressure. The Operational Taxonomic Units (OTUs) identified were primarily members of the Ascomycota phylum, comprised mostly of the Lecanoromycetes and Dothideomycetes classes. The fungal species Friedmanniomyces endolithicus, endemic to Antarctica, was found to be a marker species to the harshest conditions occurring in the shady, south exposed rock surfaces. Analysis of community composition showed that sun exposure was an environmental property that explained community diversity and structured endolithic colonization.